Mothers and Children Adherence to the Mediterranean Diet: Evidence From a Mediterranean Country - Dayi, Taygun; Soykut, Gunsu; Ozturk, Mujgan; Yucecan, Sevinc (Progress in Nutrition, 2021)
The aim of the study was to determine the effect of adherence to the Mediterranean diet of mothers on children’s adherence levels. The study was conducted with 140 mothers and preschool children in North Cyprus, which is a Mediterranean country. Adherence of mother’s to the Mediterranean diet was measured by Mediterranean Diet Adherence Screener (MEDAS) and children’s adherence was determined by the Mediterranean Diet Quality Index (KIDMED). In addition, diet diversity levels of children were evaluated with the Diet Diversity Score (DDS) scale. In mothers; 47.1% were found to have high, 37.2% moderate and 15.7% had low adherence to the Mediterranean diet. 78.6% of children showed high adherence to the Mediterranean diet. 10% of children had a high, 81.4% had moderate and 7.7% had low diet diversity. In addition, it was stated that as adherence to the Mediterranean diet of children increased, diet diversity also significantly increased (p<0.05). 80% of mothers, who were at least university graduates, had children with higher adherence and diet diversity. Moreover, the results showed that, as the adherence of mothers to the Mediterranean diet increases, adherence to the Mediterranean diet and diet diversity scores of children significantly increased (p <0.05). Since the Mediterranean diet is a dietary model in which diet diversity is easily achieved and recommended, it is an effective dietary approach that supports growth and development in childhood, and in the prevention of noncommunicable chronic diseases in adulthood period.